Disconnected and connected: Youth, News Consumption and Civic Engagement - Sebes, Marek (Civilia, 2020)
This summarizing study examines how contemporary young people use news and news media and how is this news consumption related to the level of their civic engagement. While the findings of many studies suggest that today's youth are not interested in current affairs news at all, others show a more complicated picture: young people have not lost interest in current affairs, but they differ in their access to information and in the way they move in the media environment. The study discusses the reasons for this media behavior and the implication for civic engagement of the young generation.
Keywords: News consumption; Civic engagement; Citizenship; Youth; Civic socialization; News Media; Social media